2013
DOI: 10.1089/ten.tea.2012.0104
|View full text |Cite
|
Sign up to set email alerts
|

Engineering New Bone via a Minimally Invasive Route Using Human Bone Marrow-Derived Stromal Cell Aggregates, Microceramic Particles, and Human Platelet-Rich Plasma Gel

Abstract: Tissue Engineering Part A eering new bone via a minimally invasive route using human bone marrow derived stromal cell aggregates, micro ceramic particles and human platelet rich plasma gel (doi: 10.1089(doi: 10. /ten.TEA.2012 This article has been peer-reviewed and accepted for publication, but has yet to undergo copyediting and proof correction. The final published version may differ from this proof. 2 AbstractThere is a rise in the popularity of arthroscopic procedures in orthopedics. However, the majority o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…The PRP gel itself is also an especially strong candidate for tissue engineering because it is patient-derived, chemical-free, a source of a plethora of growth factors, and can gel at a physiological temperature. Indeed, we recently demonstrated that it could be injected and gelled in situ (Chatterjea et al, 2013), and this work shows its promise for implantable bone tissue engineering.…”
Section: A Chatterjea Et Al Improved Bone Formation By Aggregated Mscsmentioning
confidence: 77%
See 1 more Smart Citation
“…The PRP gel itself is also an especially strong candidate for tissue engineering because it is patient-derived, chemical-free, a source of a plethora of growth factors, and can gel at a physiological temperature. Indeed, we recently demonstrated that it could be injected and gelled in situ (Chatterjea et al, 2013), and this work shows its promise for implantable bone tissue engineering.…”
Section: A Chatterjea Et Al Improved Bone Formation By Aggregated Mscsmentioning
confidence: 77%
“…Numerous animal studies and clinical trials have been performed to optimise the use of mesenchymal stromal cells (MSCs) for bone tissue engineering, with both revealing that the degree of bone formation is frequently inadequate (Chatterjea et al, 2010;Griffin et al, 2011;Meijer et al, 2008). One challenge is that while MSCs can be easily isolated from a variety of adult tissues and differentiated into multiple adult cell types including bone cells, their low frequency and limited propensity for osteogenic differentiation often necessitates in vitro expansion and pre-differentiation (Bruder et al, 1998;Friedenstein et al, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…This approach has recently been applied to a variety of tissues, including bone (Chatterjea et al, 2013; Dormer et al, 2012), cartilage (Cheng et al, 2011) and vasculature (Chen et al, 2013; Chamberlain et al, 2012). In the area of bone tissue engineering, a number of materials have been used in the modular format, including alginate (Man et al, 2012; Grellier et al, 2009), calcium phosphate (Jin et al, 2012) and composites (Zhou et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…79 PRP contains various important GFs that enable the growth of bone and even though the mechanism of the bone regeneration is not well understood presently, its ease of handling and application makes it a good agent in the orthopedic field. 85 In addition, it reduces inflammation, provides excellent tissue healing and being autologous reduces the risk of disease transmission and immunogenic reactions. 81 …”
Section: Platelet-rich Plasmamentioning
confidence: 99%